The Meaning of Corporate Social Responsibility (CSR): A Phenomenological Study in PT. Sejahtera Usaha Bersama Jombang - David Amrulloh; Sulastri Sulastri; Rizky Firmansyah (AIBPM Publisher, 2020)
This study aims to uncover the meaning of Corporate Social Responsibility (CSR) from the point of view of the management of PT. UB in-depth and comprehensively. The concept of CSR contained in the UUPM and UUPT will be seen in PT. Sejahtera Usaha Bersama Jombang, as a private company that is engaged in industry, especially plywood. This research uses Husserl's data analysis techniques, with epoche stages, phenomenological reduction, imagination variations, synthesis of meaning, and essence. Data collection in this study uses the method of observation, interviews, and documentation. The results found two perspectives on the meaning of CSR at PT. SUB Jombang. First, CSR is defined as an obligation that is in the form of compliance with regulations. Second, CSR is interpreted as awareness, that is the awareness of the company growing and developing in the midst of the community environment, and CSR as a charity and almsgiving.